Immune dysfunction in Niemann‐Pick disease type C. (4th June 2015) - Platt, Nick; Speak, Annelise O.; Colaco, Alexandria; Gray, James; Smith, David A.; Williams, Ian M.; Wallom, Kerri‐Lee; Platt, Frances M.
Abstract: Lysosomal storage diseases are inherited monogenic disorders in which lysosome function is compromised. Although individually very rare, they occur at a collective frequency of approximately one in five thousand live births and usually have catastrophic consequences for health. The lysosomal storage diseases Niemann‐Pick disease type C (NPC) is caused by mutations predominantly in the lysosomal integral membrane protein NPC1 and clinically presents as a progressive neurodegenerative disorder. In this article we review data that demonstrate significant dysregulation of innate immunity in NPC, which occurs both in peripheral organs and the CNS. In particular pro‐inflammatory responses promote disease progression and anti‐inflammatory drugs provide benefit in animal models of the disease and are an attractive target for clinical intervention in this disorder. Niemann‐Pick disease type C is a rare, devastating, inherited lysosomal storage disease with a unique cellular phenotype characterized by lysosomal accumulation of sphingosine, various glycosphingolipids and cholesterol and a reduction in lysosomal calcium. In this review we highlight the impact of the disease on innate immune activities in both the central nervous system (CNS) and peripheral tissues and discuss their contributions to pathology and the underlying mechanisms. Abstract : Niemann‐Pick disease type C is a rare, devastating, inherited lysosomal storage disease with a unique cellular phenotype characterized by lysosomal accumulation of sphingosine, various glycosphingolipids and cholesterol and a reduction in lysosomal calcium. In this review we highlight the impact of the disease on innate immune activities in both the central nervous system (CNS) and peripheral tissues and discuss their contributions to pathology and the underlying mechanisms. This article is part of the Special Issue "Neuroinflammation – A Two Way Street Directing CNS Injury and Repair".